2015
DOI: 10.1177/1748006x15598722
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of minimal cut and path sets based on direct partial Boolean derivatives

Abstract: Principal steps in reliability engineering include estimation of system reliability and identification and quantification of situations which cause a system failure. There are several techniques that can be used to solve these tasks. Some of them are based on minimal cut (path) sets, which represent minimal sets of basic events, whose simultaneous occurrence leads to a failure (repair) of the system. In this article, applications of minimal cut (path) sets in reliability analysis are summarized, and their conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Authors of studies [2,5,6] shown that the reliability analysis of system can be implemented by application of Logical Differential Calculus. The algorithms for calculation of frequency indices have been studied in [6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Authors of studies [2,5,6] shown that the reliability analysis of system can be implemented by application of Logical Differential Calculus. The algorithms for calculation of frequency indices have been studied in [6].…”
Section: Introductionmentioning
confidence: 99%
“…The algorithms for calculation of frequency indices have been studied in [6]. The definition and computation of IMs based on Logical Differential Calculus, in particular Direct Partial Boolean Derivatives (DPBD), have been proposed and investigated in [2,5]. These derivatives allow investigating of the function value change depending on the change of the value of the function variable.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Minimal path sets are obtained by incidence-matrix method and then inverted to minimal cut sets in [9,10]. Literature [11] summarizes the applications of minimal cut sets and proposes a new algorithm for minimal cut sets based on correlation with direct partial Boolean. Literature [12] proposes a new algorithm based on Boolean satisfiability problem to solve the minimal cut sets in fault tree analysis.…”
Section: Introductionmentioning
confidence: 99%